IMPLEMENTASI JADWAL SPEEDBOAT DAN PEMAKAIAN BAHAN BAKAR PADA PT. METALINDO BUMI RAYA - Dwi Retnosari (INFO-TEKNIK, 2018)
PT. Metalindo Bumi Raya is a mining company operating on the island of sebuku. Speedboat Port PT. Metalindo Bumi Raya has a problem of speedboat schedule information system, making it difficult and slow in the process of reporting passenger data, drivers, schedules, fuel purchases, spare parts purchases. The development of information technology is currently growing very rapidly and the need for computer technology is increasingly in demand by the company, in line with the existing system problems when it needs to be balanced with the existence of a system that can monitor the speedboat schedule of employees and information on the use of fuel at PT. Metalindo Bumi Raya. Methods built for Research Implementation of Speedboat schedule and fuel usage at PT. Metalindo Bumi Raya uses several stages of research that identify problems, planning, data collection, system analysis and system design. Making the implementation of speedboat schedule reporting system and fuel consumption at PT. Metalindo Bumi Raya uses delphi 7, and MYSQL as database. Reporting of data reporting of passenger data, driver, schedule, fuel purchase, sparepart purchase at PT. Metalindo Bumi Raya will be able to walk more easily so it can help the officers in carrying out their duties.